Preparation and characterization of acrylic pressure-sensitive adhesives based on UV and heat curing systems. (June 2017) - Lee, Seo Ho; You, Ryong; Yoon, Young Il; Park, Won Ho
Abstract: UV curable acrylic oligomers were prepared for a dual-crosslinking system applicable to general thermosetting acrylic pressure-sensitive adhesives (PSAs). UV-curable oligomers were synthesized using isophorone diisocyanate (IPDI), acrylate monomers, and propylene imine (PI). Acrylate monomers were added at a constant rate to one isocyanate group of IPDI for selective binding, and a polymerization inhibitor was added to prevent polymerization. Also, binding sites bound to the adhesive backbone were generated by adding PI at a constant rate after solvent addition. The synthesized UV oligomers were confirmed by ATR-FTIR spectroscopy. In addition, dual-curable PSA tapes were prepared by simply blending UV curable oligomers and thermosetting acrylic PSAs at room temperature, and their mechanical properties (gel fraction, ball tack, 180° peel strength, and shear adhesion failure temperature (SAFT)) were evaluated based on the volume of UV curable oligomers.